2018
DOI: 10.1038/s41467-018-05027-5
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous mechanical behavior of nanocrystalline binary alloys under extreme conditions

Abstract: Fundamentally, material flow stress increases exponentially at deformation rates exceeding, typically, ~103 s−1, resulting in brittle failure. The origin of such behavior derives from the dislocation motion causing non-Arrhenius deformation at higher strain rates due to drag forces from phonon interactions. Here, we discover that this assumption is prevented from manifesting when microstructural length is stabilized at an extremely fine size (nanoscale regime). This divergent strain-rate-insensitive behavior i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The material for this study was processed through mechanically alloyed powders using a multi-pass high-temperature equal channel angular extrusion (ECAE) at 700°C. Complete details of the powder processing and consolidation efforts can be found in 5,35 and also Supplementary Methods. Primary microstructural analysis of the as-consolidated test samples using transmission electron microscopy (TEM, see Supplementary Methods) indicates that the extruded microstructure for this alloy was found to have an average grain size of 87 ± 15 nm with Ta based nanoclusters having an average diameter of 3.2 ± 0.9 nm, see Supplementary Methods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The material for this study was processed through mechanically alloyed powders using a multi-pass high-temperature equal channel angular extrusion (ECAE) at 700°C. Complete details of the powder processing and consolidation efforts can be found in 5,35 and also Supplementary Methods. Primary microstructural analysis of the as-consolidated test samples using transmission electron microscopy (TEM, see Supplementary Methods) indicates that the extruded microstructure for this alloy was found to have an average grain size of 87 ± 15 nm with Ta based nanoclusters having an average diameter of 3.2 ± 0.9 nm, see Supplementary Methods.…”
Section: Resultsmentioning
confidence: 99%
“…For moderate to high shock stresses, such as those reported in this letter, plastic deformation is governed by the mobile dislocation density and the average mobile dislocation velocity (approaching the shear wave velocity) through the classical Orowan relationship (_ ε ¼ bρν, where _ ε is the applied strain rate, b is the Burgers vector, ρ is the dislocation density, and ν is the dislocation velocity). However, using atomistic simulations, it was recently predicted that NC-Cu-Ta alloys exhibit a reduced dislocation gliding velocity stemming from the stability of the controlling microstructural length scale such as the grain size and Ta nanocluster size/spacing, which act as barriers that pin/slow down defect propagation 35 . In addition, it was also shown that the introduction of Ta clusters as well as the increased grain boundary volume results in an increased phonon density of states such that phonon-drag forces would play a larger role on mobile dislocations in NC-Cu-Ta alloys through an increased drag coefficient 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[83,100,101] These all serve to increase the alloy's stability against grain growth at high homologous temperatures (> 0.5 T/T m ) or, in some cases, suppress detrimental phase transformations, [102] besides also imparting many other exceptional mechanical properties. [103][104][105][106][107] A recent perspective piece by Spearot et al [108] specifically speaks to the mechanical properties of stabilized fcc metals, and some unexplored future research needs and opportunities. Some intriguing ideas presented include understanding the role of chemistry on the transition between dislocation-based plasticity and grain boundary-mediated plasticity in thermally stable alloys, along with appropriate constitutive models that also account for this transition.…”
Section: Low On Energy: Thermodynamic (And Kinetic) Pathways To mentioning
confidence: 99%
“…3. The deformation mechanisms and mechanical properties of thermally stable alloys are only just being uncovered, and it is critical to continue explorations of the stability of the stable nanocrystalline grains under mechanical loading environments, such as wear, [105,111] fatigue, [61] creep, [106] high-strain rates, [107] irradiation, [112,113] and high pressures, and to critically compare the findings with the more traditionally processed NC materials.…”
Section: A Potential Openings For Studymentioning
confidence: 99%